Effect of Corporate Social Responsibility on Sustainable Community Development in Zambia: A Case Study of Eco-Bank. - Lukonga, Munalula; Musonda, Bryson (International Journal of Poverty, Investment and Development, 2024)
Purpose: ECOBANK, a prominent financial institution in Africa, has positioned itself as a socially responsible entity alongside its financial success. This study explored the impact of ECOBANK's Corporate Social Responsibility (CSR) initiatives on sustainable community development in Zambia. Methodology: The objectives were to examine specific CSR initiatives, investigate underlying motivations, and determine local community perceptions. Employing a mixed-methods approach, the study engaged 11 ECOBANK employees, and 22 community members. Questionnaire and interview guide were used to collect data. Data collected was managed with Microsoft Excel, and SPSS v27.0 was utilized to analyze the data. One sample t-test was performed to determine the perception of local community members on the impact of ECOBANK's CSR activities. Findings: ECOBANK exhibits proactive and diverse CSR engagement, ranging from education to environmental sustainability. Employee awareness is commendably high, emphasizing effective internal communication. The primary motivation identified is public image enhancement. Simultaneously, societal responsibility, regulatory compliance, and community development emerged as recognized drivers. The one-sample t-test showed a significant difference in local community perceptions of ECOBANK's CSR impact on Sustainable Community Development. The p-value of 0.000096 (less than 0.05) indicates the observed differences are unlikely by chance, strengthening the findings. The mean difference of 10.500 suggests a favorable perception exceeding the benchmark of 70%. Unique Contribution to Theory, Practice, and Policy: The study concludes that ECOBANK's CSR initiatives effectively position it as a responsible corporate citizen in Zambia, aligning with sustainable development goals and fostering positive employee perceptions. ECOBANK's motivations for CSR involvement encompass a strategic focus on public image enhancement, societal responsibility, regulatory compliance, and community development. Local community members perceive ECOBANK's CSR activities positively, indicating a favorable influence on sustainable community development.